O professor articulador de aprendizagem na escola pública estadual de Primavera do Leste/MT - Szpakowski, Janaína (2018)
This research is linked to the Postgraduate Program in Education (PPGEdu/CUR/UFMT) on the Formation of Teachers and Public Educational Policy and its object of study is to investigate how the pedagogical practice of the Learning Articulator is built in the public school of the state education network, of the city of Primavera do Leste/MT. This professional works with students that show learning challenges and that need pedagogical support. Considering the central objective, the leading of the research rules on the following specific objectives: a) Identify how was insertion and declined the Learning Articulator function in the Human Cycle Policy; b) Understanding how the Learning Articulator conceives its function; c) Comprehending about the conceptions that ground of the Learning Articulator practice; d) Analyzing how the Learning Articulator is being developed in the context of the Human Cycle Policy practice in the public school of the state education network, of the city of Primavera do Leste/MT. To the data collect were used the instruments, which are: questionnaire, memorial semi structured interview and documentary analysis, because they are important components in the accomplishment of the qualitative research, thus obtaining objective and subjective data. The dissertation text is organized in three chapters: in the first one, methodological delineated the path covered by the research, which is qualitative approach, based on dialectical / philosophical thinking of Paulo Freire. And still the method adopted, the instruments used and the subjects of the research. In the following chapter, of theoretical character, I make a brief historical rescue of the politics of curricular organization in cycles at national and state level, with emphasis on the role of the Learning Articulator in this context. In the third chapter, I dialogue with the data of the research seeking to interpret and understand them from the perspective of a dialectical movement, which considers the historical contradictions of educational practice, immersed in a complex and polarized reality. The analysis of the collected data shows that the construction of the pedagogical practice of the Learning Articulator, the objective conditions of work, offered by both the school and public policy, interpersonal relationships that it establishes in the school environment and necessarily, so that it can transform its practice into an object of analysis, reflection and understanding based on a theoretical framework. The critical reflection on the practice involves becoming aware of the actions that involve the actions, relations between doing and know-how that can be manipulated. The ideal is that lifelong learning enables this exercise to distance itself from the practical context, to theoretically apprehend it, in a movement in which theory and praxis are mutually fertilized.